Blood serum components and serum protein test of Hybro-PG broilers of different ages - Silva, PRL [UNESP]; Freitas Neto, OC [UNESP]; Laurentiz, AC [UNESP]; Junqueira, Otto Mack [UNESP]; Fagliari, JJ [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
Blood serum samples of HYBRO PG broilers were analyzed, with 30 samples collected from 21-day-old broilers (G1), 30 from 35-day-old birds (G2), and 30 from 42-day-old birds (G3), with the aim of establishing normal values of some blood serum parameters. The activities of the enzymes gamma-glutamyl-transferase (GGT), aspartate aminotransferase (AST), creatine kinase (CK), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH), serum levels of total calcium, calcium ion, phosphorus, sodium, potassium, magnesium, chlorides, creatinine, uric acid, triglycerides, cholesterol, total protein, albumin, total and indirect and direct bilirubin, and electrophoretic profile of serum proteins in acrylamide (SDS-PAGE) and agarose gel were determined. There was no influence of age on total bilirubin and albumin levels. All the other evaluated parameters presented differences in at least one age group. Protein electrophoretic profile also changed as a function of age. The obtained results can be considered as normal for the studied ages, and therefore be used as references for the interpretation of laboratory exams of broilers of this genetic line in the evaluated ages.
Keywords: Broiler; Serum biochemistry; serum protein test